(untitled) (LACCEI, 2024)
The purpose of this business case is to identify the best alternative to optimize the inventory management of the products manufactured and commercialized by ABC Dermocosmetics Laboratory. The methodology used was the Harvard Business Case, which analyzed the alternatives proposed by the interest group and their applicability under a strategic and financial approach. The chosen alternative was to make an improvement to the current ERP, since it facilitates the integration of processes, improves the level of customer service, and increases profitability.